Peripheral Demyelinating Diseases: From Biology to Translational Medicine - Kamil, Khidhir; Yazid, Muhammad Dain; Idrus, Ruszymah Bt Hj; Das, Srijit; Kumar, Jaya (Frontiers in Neurology, 2019)
Demyelinating diseases represent a spectrum of disorders that impose significant burden on global economy and society. Generally, the prognosis of these diseases is poor and there is no available cure to date. In the few last decades, a plethora of studies has shed some light on the biology and physiology of Schwann cells and its neuroprotective effects in the peripheral nervous system (PNS). Insults to the PNS by various infectious agents, genetic predisposition and immune-related mechanisms jeopardize Schwann cell functions and cause demyelination. To date, there is no effective and reliable biomarkers for PNS-related diseases diagnosis, monitoring and prognosis. Therefore, we aim to review the following in this manuscript: pathogenesis of various types of peripheral demyelinating diseases such as Guillain-Barre syndrome, Chronic Inflammatory Demyelinating Polyradiculoneuropathy, Anti-Myelin Associated Glycoprotein Neuropathy, POEMS syndrome, and Charcot-Marie-Tooth disease; emerging novel biomarkers for peripheral demyelinating diseases, and Schwann cell associated markers for demyelination.